Single-cell genetic expression of mutant GABAA receptors causing Human genetic epilepsy alters dendritic spine and GABAergic bouton formation in a mutation-specific manner - Lachance-Touchette, Pamela; Choudhury, Mayukh; Stoica, Ana; Di Cristo, Graziella; Cossette, Patrick (Frontiers in Cellular Neuroscience, 2014)
Mutations in genes encoding for GABAA receptor subunits is a well-established cause of genetic generalized epilepsy. GABA neurotransmission is implicated in several developmental processes including neurite outgrowth and synapse formation. Alteration in excitatory/inhibitory synaptic activities plays a critical role in epilepsy, thus here we investigated whether mutations in α1 subunit of GABAA receptor may affect dendritic spine and GABAergic bouton formation. In particular, we examined the effects of three mutations of the GABRA1 gene (D219N, A322D and K353delins18X) that were found in a cohort of French Canadian families with genetic generalized epilepsy. We used a novel single-cell genetic approach, by preparing cortical organotypic cultures from GABRA1flox/flox mice and simultaneously inactivating endogenous GABRA1 and transfecting mutant α1 subunits in single glutamatergic pyramidal cells and basket GABAergic interneurons by biolistic transfection. We found that GABRA1−/− GABAergic cells showed reduced innervation field, which was rescued by co-expressing α1-A322D and α1-WT but not α1-D219N. We further found that the expression of the most severe GABRA1 missense mutation (α1-A322D) induced a striking increase of spine density in pyramidal cells along with an increase in the number of mushroom-like spines. In addition, α1-A322D expression in GABAergic cells slightly increased perisomatic bouton density, whereas other mutations did not alter bouton formation. All together, these results suggest that the effects of different GABAAR mutations on GABAergic bouton and dendritic spine formation are specific to the mutation and cannot be always explained by a simple loss-of-function gene model. The use of single cell genetic manipulation in organotypic cultures may provide a better understanding of the specific and distinct neural circuit alterations caused by different GABAA receptor subunit mutations and will help define the pathophysiology of genetic generalized epilepsy syndromes.